2020
DOI: 10.1021/jacs.0c08510
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Functional Impurities for Fast and Efficient Incorporation of Manganese into Quantum Dots

Abstract: The incorporation of manganese (Mn) ions into Cd­(Zn)-chalcogenide QDs activates strong spin-exchange interactions between the magnetic ions and intrinsic QD excitons that have been exploited for color conversion, sunlight harvesting, electron photoemission, and advanced imaging and sensing. The ability to take full advantage of novel functionalities enabled by Mn dopants requires accurate control of doping levels over a wide range of Mn contents. This, however, still represents a considerable challenge. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(134 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, as highlighted by the fitting procedure shown in Figure b for [Mn 2+ ] = 20%, a third narrow component emerges for [Mn 2+ ] > 10% and intensifies with increasing Mn 2+ content (Figure c). The correlation between the intensity of such a component and the concentration of magnetically active dopants in the NC lattice suggests that it originates from short-range exchange narrowing coupling between nearby Mn 2+ centers. Whereas the long-range dipolar component is almost insensitive to the Mn 2+ content, the intensity of the exchange coupling signal anticorrelates with the intensity of the sextet due to nearly isolated Mn 2+ ions, eventually disappearing for [Mn 2+ ] = 40%. This suggests that a growing fraction of isolated dopant ions gradually turns into adjacent exchange-coupled centers.…”
mentioning
confidence: 99%
“…Interestingly, as highlighted by the fitting procedure shown in Figure b for [Mn 2+ ] = 20%, a third narrow component emerges for [Mn 2+ ] > 10% and intensifies with increasing Mn 2+ content (Figure c). The correlation between the intensity of such a component and the concentration of magnetically active dopants in the NC lattice suggests that it originates from short-range exchange narrowing coupling between nearby Mn 2+ centers. Whereas the long-range dipolar component is almost insensitive to the Mn 2+ content, the intensity of the exchange coupling signal anticorrelates with the intensity of the sextet due to nearly isolated Mn 2+ ions, eventually disappearing for [Mn 2+ ] = 40%. This suggests that a growing fraction of isolated dopant ions gradually turns into adjacent exchange-coupled centers.…”
mentioning
confidence: 99%
“…It has been shown that secondary phosphines can increase the nucleation and growth rate of CdSe QDs compared with tertiary phosphines (such as TOP). [ 57,58 ] We verified that this also applies to the synthesis of CdSe NRs (Scheme S1, Supporting Information). As sketched in Figure 1f, the formation of colloidal CdSe NRs, as for nanocrystals in general, occurs at least in three stages, including monomer formation, nucleation and growth.…”
Section: Resultsmentioning
confidence: 60%
“…The magnitudes of the -C coupling constants (−21.1 cm −1 ≡ 2.6 meV, and −8.2 cm −1 ≡ 1.0 meV) are similar to the coupling constants obtained from magnetic susceptibility measurements on Mn-doped ZnSe QDs, for which values between −19.5 cm −1 and −13.5 cm −1 were reported, with varying dopant concentration. 61 Moreover, antiferromagnetic coupling was also reported in Mn-doped ZnS 26 and CdSe; 27,62 however, no coupling constants were extracted.…”
Section: Resultsmentioning
confidence: 99%